Effect of s-Klotho Protein, GPX, Visfatin, Leptin and ROS of Iraqi Women with Breast Cancer - Ascar , Israa F.; Fadhel , Suha Nasser (Iraqi Journal of Science, 2024)
The most prevalent cancer is breast cancer, and the incidence of breast cancer in women worldwide is increasing at a remarkably rapid rate. This study was conducted on 90 samples (45 newly diagnosed breast cancer samples and 45 control group samples), ranging in age from 35 to 70 years. Blood samples were collected from the Alawia Teaching Hospital and the Oncology Teaching Hospital between October 2020 and March 2021. ELISA assessed ROS, GPX, visfatin, IGF-1, vitamin A, leptin, and soluble al-Klotho. The results indicate that the breast cancer patients had significantly higher (ROS 3.57, visfatin 17.44) (ng/mL) (p<0.0001) and leptin 16.11 (ng/mL). In the group of patients, there was a significant increase (p<0.004) compared with the control group, whereas there were no significant differences between IGF-1 (624.72 pg/mL) (p>0.507), s-Klotho 398.22 ng/L (p>0.653), and vitamin A 69.49 umol/L (p<0.05). The results showed a negative correlation among the levels of patients with BC (ROS and vitamin A, GPX, IGF-1, GPX, leptin, and vitamin A). Finally, the current study concludes that vitamin A deficiency is one of the important factors that may influence the clinical evolution and prognosis of patients with breast cancer. Moreover, it was shown that the higher levels of leptin and visfatin could increase the danger in BC cases. The study measured levels of leptin and visfatin, which can increase the danger in BC cases, and measured ROS in patients.